Mediação na ouvidoria unversitária: gestão de conflitos na Universidade Regional do Cariri. - Ferreira, Andersson Belém Alexandre (2024)
The 1988 Federal Constitution values the citizen, guaranteeing them tools for popular participation, control, and conflict resolution. In this context, university ombudsmen represent democratic mechanisms for exercising citizenship by bringing the citizen-user closer to the Public Administration, promoting debureaucratization, and facilitating the management of demands through new forms of conflict resolution, particularly conflict mediation. However, for the University to fulfill its public purpose of acting as a channel of interlocution and using conflict mediation within the conflicting sphere of a Higher Education Institution, it is essential that this body has institutional maturity. Based on the relevant legislation and an analysis of management reports from 2018 to 2022, this research set out to assess the level of institutionality of the University Ombudsman at the Universidade Regional do Cariri-URCA, with a view to using mediation as a consensual form of conflict resolution. To achieve the general objective, specific objectives were defined, which are: 1) to verify the current state of URCA's ombudsman's office in terms of structure, staff, and institutional provision; 2) to examine the compatibility of mediation as a conflict resolution tool by the university ombudsman; and 3) to propose improvements through a technical product in order to contribute to the institutionalization of URCA's University Ombudsman. The research has a qualitative approach and, in terms of its aims, has the characteristics of descriptive and exploratory research. The data was interpreted using the content analysis technique. The results lead to the conclusion that conflict mediation is compatible with the simplicity and reduction of bureaucracy in the University Ombudsman's Office, strengthening dialogue. However, URCA's ombudsman is not properly institutionalized, as it does not have its own regulations, structure, and staff, and there are still no explicit criteria for the appointment of the head ombudsman, which hampers the implementation of mediation in the current University Ombudsman's Office. As a result of these reflections, an Executive Summary was produced with the main suggestions to precede the use of mediation as a means of resolving conflicts, in order to collaborate with the body and the respective HEI.